RAPD analysis of eleven iranian pomegranate (Punica granatum L.) cultivars - Sheidai, Masoud (Acta Biologica Szegediensis, 2007)
RAPD markers variations were studied in eleven pomegranate cultivars. Fifteen RAPD primers used out of which 13 primers could produce bands. In total 173 bands were produced out of which 73 bands were common in all the cultivars while 6 bands were specific, which may be used in the cultivars discrimination. Primers OPB12 and OPA13 produced the highest number of polymorphic bands (12 bands out of 16=0.75% and 11 bands out of 25=0.44), while primers OPR15 and OPA15 produced the least number of polymorphic bands (2 out of 12=0.16%). Different similarity coefficients determined among the cultivars studied, showed the highest value of similarity between cultivars Khatooni and Anbari as well as between Khatooni and Atabaki (r=0.94) while the lowest value of similarity occurred between the cultivars Sefid and Bihaste as well as Sefid and Khatooni (r = 0.62). Different clustering methods showed distinctness of the olive cultivars studied.